Hollow particles, medium for plant cultivation
Hollow particles with a TAC outer shell address the challenges of water retention and drainage in plant cultivation media, offering excellent biodegradability and reduced environmental impact.
Patent Information
- Application Number
- JP2021053179
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-26
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2041-03-26
AI Technical Summary
Existing plant cultivation media using synthetic polymer particulates or fibers face challenges in achieving both excellent water retention and drainage properties, and biodegradability.
Development of hollow particles with an outer shell made of triacetylcellulose (TAC) that have a specific surface area, bulk density, and through holes, enhancing water retention and drainage properties.
The hollow particles demonstrate excellent water retention and drainage properties, making them suitable for use as a biodegradable plant cultivation medium, while also reducing the weight and environmental impact of the medium.
Smart Images

Figure 0007656460000001 
Figure 0007656460000002
Abstract
Description
[Technical field]
[0001] The present invention relates to hollow particles and a medium for cultivating plants. [Background technology]
[0002] Microplastics, which are particles or fibers formed using synthetic polymers, are used in a wide range of applications, including cosmetic ingredients, resin additives, paints, abrasives, lightweight agents, and water and oil absorbents. On the other hand, in recent years, there are concerns that these microplastics are causing marine pollution, and that they may be ingested by aquatic organisms such as plankton and fish, and ultimately migrate into the human body. As a result, there are moves in various countries, including Japan, to restrict the use of synthetic polymers and plastics.
[0003] In light of the above, attempts are being made to expand the use of materials that have the property of being biodegradable in the natural environment (in soil, fresh water, and seawater). Representative biodegradable resins include cellulose acetates such as triacetyl cellulose (TAC). For example, Patent Document 1 describes an invention relating to cellulose acetate particles whose average particle size, sphericity, surface smoothness, and total degree of acetyl substitution are each specified. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6609726 Summary of the Invention [Problem to be solved by the invention]
[0005] There is a known technology that uses synthetic polymer granules or fibers as a medium for plant cultivation instead of natural soil. A medium for plant cultivation is required to have two contradictory functions: excellent water retention to hold as much water as plants can use, and excellent drainage or permeability to quickly remove water from the medium after the plant has taken up the water it needs. The present inventors attempted to use cellulose acetate particles as a culture medium for cultivating plants and found that although they have the advantage of being biodegradable, there is room for further improvement in terms of achieving both the above-mentioned water retention and drainage properties when used as a culture medium for cultivating plants.
[0006] In view of the above circumstances, an object of the present invention is to provide hollow particles having excellent water retention and drainage properties. Another object of the present invention is to provide a plant cultivation medium containing the hollow particles. [Means for solving the problem]
[0007] As a result of extensive investigation into the above problems, the present inventors have found that the above problems can be solved by the following configuration.
[0008] [1] A hollow particle having an outer shell containing triacetyl cellulose, the outer shell having through holes penetrating the outer shell in a thickness direction, and a specific surface area of the hollow particle being 0.02 m 2 / g or more, and the bulk density of the hollow particles is 0.90 g / cm 3 Below are the hollow particles. [2] The hollow particles according to [1], wherein a ratio t / R of a thickness t of the outer shell to an average particle diameter R of the hollow particles is 0.10 to 0.40. [3] The bulk density of the hollow particles is 0.30 to 0.90 g / cm 3 3. The hollow particle according to claim 1 or 2, [4] The specific surface area of the hollow particles is 0.02 to 5 m 2 / g. [5] The hollow particles according to any one of [1] to [4], wherein a ratio t / R of a thickness t of the outer shell to an average particle diameter R of the hollow particles is 0.13 to 0.40. [6] The hollow particles according to any one of [1] to [5], wherein the average particle size R of the hollow particles is 1 to 600 μm. [7] A medium for cultivating plants, comprising the hollow particles according to any one of [1] to [6]. Effect of the Invention
[0009] According to the present invention, hollow particles having excellent water retention and drainage properties can be provided. Also, according to the present invention, a plant cultivation medium containing the hollow particles can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below. The following description of the components may be based on representative embodiments of the present invention, but the present invention is not limited to such embodiments. In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits. In this specification, when two or more types of a component are present, the "content" of the component means the total content of those two or more components. In this specification, the "saturated vapor pressure" of a certain component means the saturated vapor pressure (unit: kPa) of that component at 20°C.
[0011] [Hollow particles] The hollow particles according to the present invention (hereinafter also referred to as "the present hollow particles") have an outer shell containing triacetyl cellulose (hereinafter also referred to as "TAC"), and the outer shell has through holes penetrating the outer shell in the thickness direction. 2 / g or more, and the bulk density of the hollow particles is 0.90 g / cm 3 The following is the result.
[0012] The present inventors have conducted extensive research into suitable embodiments for using hollow particles containing cellulose acetate as a culture medium for plant cultivation, and have found that, as described above, hollow particles containing TAC and having an outer shell with the above-mentioned through holes, and further having a specific specific surface area and bulk density, have excellent water retention and drainage properties as a culture medium for plant cultivation. Although the reason why hollow particles having the above-mentioned characteristics exhibit the effect of excellent water retention and drainage properties is not clear in detail, the present inventors speculate as follows. That is, the hollow particles have cavities that have the function of retaining water, and have a specific specific surface area, so it is presumed that the hollow particles retain a large amount of water and have excellent water retention. In addition, the hollow particles have a specific bulk density, so that many voids exist between and inside the hollow particles, so it is presumed that water is quickly discharged through these voids. Furthermore, the cavities of the hollow particles communicate with the outside of the hollow particles through through holes formed in the outer shell, so it is presumed that water retained in the hollow parts can be quickly discharged. The hollow particles according to the present invention will be described in detail below. In this specification, the term "excellent effect of the present invention" refers to a plant cultivation medium having excellent water retention or drainage properties.
[0013] In this specification, the term "hollow particle" means that a cavity is formed inside the particle and that the ratio t / R of the shell thickness t to the average particle diameter R of the particle measured by the method described below is 0.45 or less.
[0014] [Outer shell] The hollow particles have a hollow structure in which the cavity is covered with an outer shell. The shell constituting the hollow particles preferably contains TAC and is substantially composed of TAC. More specifically, the content of TAC in the hollow particles is preferably 80% by mass or more, more preferably 90% by mass or more, based on the total mass of the hollow particles (equal to the total mass of the shell). The upper limit is not particularly limited, and may be 100% by mass based on the total mass of the hollow particles.
[0015] <Triacetyl cellulose (TAC)> In this specification, "triacetyl cellulose (TAC)" refers to a cellulose acylate in which the hydrogen atoms constituting the hydroxyl groups of cellulose, i.e., the free hydroxyl groups at the 2nd, 3rd and 6th positions of β-1,4-bonded glucose units, are replaced with acetyl groups, and the degree of substitution of the acetyl groups is 2.6 or more. Here, the "substitution degree" refers to the degree of substitution of acetyl groups for hydrogen atoms constituting hydroxyl groups of cellulose. 13 It can be calculated by comparing the area intensity ratio of carbon of cellulose acylate measured by C-NMR method.
[0016] The degree of substitution of TAC contained in the present hollow particles is preferably 2.6 to 2.9, and more preferably 2.8 to 2.9, in that both water absorbency and quick drying properties can be achieved and biodegradability is superior. The degree of substitution of TAC can be appropriately adjusted by known methods such as changing the partial hydrolysis time during synthesis of TAC and alkaline saponification.
[0017] The weight average molecular weight (Mw) of TAC is not particularly limited, but from the viewpoint of the mechanical strength of the hollow particles, it is preferably 100,000 or more, and more preferably 100,000 to 500,000. The dispersity, which is the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the TAC, is preferably from 1.0 to 5.0, and more preferably from 1.0 to 4.0. In this specification, the weight average molecular weight and number average molecular weight are molecular weights measured by gel permeation chromatography (GPC).
[0018] TAC can be produced by a known method for producing cellulose acetate. For example, the so-called acetic acid method uses acetic anhydride as an acetylating agent, acetic acid as a diluent, and sulfuric acid as a catalyst. The basic steps of the acetic acid method are: (1) a pretreatment step in which a pulp raw material (dissolving pulp) having a relatively high α-cellulose content is disintegrated and crushed, and then acetic acid is sprayed and mixed; (2) an acetylation step in which the pretreated pulp of (1) is reacted with a mixed acid consisting of acetic anhydride, acetic acid, and an acetylation catalyst (e.g., sulfuric acid); (3) an aging step in which cellulose acetate is hydrolyzed to cellulose acetate having a desired acetylation degree; and (4) a posttreatment step in which the cellulose acetate after the hydrolysis reaction is precipitated from the reaction solution, purified, stabilized, and dried. For the raw materials and manufacturing method of TAC, see pages 7 to 12 of the Japan Institute of Invention and Innovation's Technical Bulletin (Technical Publication No. 2001-1745, published on March 15, 2001, Japan Institute of Invention and Innovation), the disclosure of which is incorporated herein by reference.
[0019] <Other ingredients> The shell may contain components other than TAC, as long as they do not impair the functions of the hollow particles, particularly the water retention and drainage properties. Examples of components other than TAC include cellulose acylates other than TAC. Here, "cellulose acylate" refers to a cellulose ester in which some or all of the hydrogen atoms constituting the hydroxyl groups of cellulose, i.e., the free hydroxyl groups at the 2nd, 3rd and 6th positions of β-1,4-bonded glucose units, are substituted with acyl groups. The degree of substitution of acyl groups in cellulose acylate other than TAC (hereinafter also referred to as "degree of acylation") is preferably 2.6 or more, more preferably 2.6 to 2.9.
[0020] Examples of the acyl group include an acetyl group (provided that the degree of substitution of the acetyl group is less than 2.6), a propionyl group, and a butyryl group. The acyl group substituted in the cellulose acylate other than TAC may be of one type alone or a combination of two or more types.
[0021] When the present hollow particles contain a cellulose acylate other than TAC, the content thereof is preferably 10% by mass or less based on the total mass of the present hollow particles. The hollow particles may contain impurity components that are unintentionally mixed in during the manufacturing process. Examples of impurity components include solvents contained in the dope used to manufacture the hollow particles. The content of impurity components is preferably 1% by mass or less based on the total mass of the hollow particles, and more preferably, the hollow particles are substantially free of impurity components.
[0022] <Outer shell composition> The shell has through holes penetrating the shell in the thickness direction. The shell having through holes in the thickness direction facilitates the movement of water in and out of the hollow particles, thereby improving the water retention and drainage properties of the hollow particles. The number and size of the through holes are not particularly limited as long as water can easily move through them. In order to obtain a more excellent effect of the present invention, it is preferable that the shell has a plurality of through holes. In order to obtain a well-balanced excellent effect of the present invention and particle strength, it is preferable that the diameter of the through holes is 1 to 10% of the average particle diameter R of the hollow particles. The number and size of the through holes formed in the outer shell can be controlled, for example, in the hollow particle manufacturing method described below, by adjusting conditions such as the combination and content of the good solvent and the poor solvent, the extrusion atmosphere temperature, and the extrusion environment (in dry air, in a solvent atmosphere, in a coagulation liquid, etc.).
[0023] The thickness t of the outer shell can be appropriately selected depending on the average particle diameter R of the hollow particles, and is preferably adjusted so that the ratio t / R of the thickness t of the outer shell to the average particle diameter R falls within the preferred range described below. More specifically, the thickness of the outer shell is preferably 0.1 to 200 μm, and more preferably 0.15 to 150 μm. The thickness t of the outer shell can be measured from a cross-sectional image obtained by observing the cross section of a hollow particle using an electron microscope, as described in the Examples below. The thickness t of the shell can be controlled by adjusting conditions such as the combination and content of the good solvent and the poor solvent, the solid content of the dope, the drying temperature, and the amount of the solvent relative to the drying gas during drying in the method for producing hollow particles described later.
[0024] [Structural features] The hollow particles have a hollow portion that is a cavity surrounded by an outer shell. The hollow particles have excellent water retention due to the hollow parts having the function of retaining water. Furthermore, as described above, the hollow parts communicate with the outside of the hollow particles via the through holes formed in the outer shell, and therefore water can easily move into the hollow parts and can easily be discharged from the hollow parts, so the hollow particles have excellent drainage properties.
[0025] The specific surface area of this hollow particle is 0.02m 2 The hollow particles have the above specific surface area, and hence have a large area in contact with water, thereby exhibiting excellent water retention. The specific surface area of the hollow particles is preferably 0.025 m2 or less, which is a better advantage of the present invention. 2 / g or more is preferable, and 0.03m 2 The specific surface area of the hollow particles is preferably 5 m / g or more in terms of superior drainage. 2 / g or less is preferable, and 1m 2 / g or less is more preferable.
[0026] The specific surface area of hollow particles is the BET specific surface area (unit: m) per mass of hollow particles measured by the nitrogen adsorption BET single point method. 2 / g). The specific surface area measuring device is not particularly limited, and an example thereof is a specific surface area measuring device ("SA-1000" manufactured by Shibata Rikagaku Co., Ltd.). The specific surface area of the hollow particles can be controlled by adjusting conditions such as the combination and content of a good solvent and a poor solvent, the solid content of the dope, the drying temperature, and the amount of the solvent relative to the drying gas during drying in the method for producing hollow particles described later.
[0027] The bulk density of the hollow particles is 0.90 g / cm3 The hollow particles have the above bulk density, and therefore have many voids between and inside the hollow particles, which allows for better drainage (permeability) during drainage. Therefore, for example, when the hollow particles are used as a medium for cultivating plants, drainage proceeds quickly, breathability is maintained even in the medium, excessive humidity rise in the medium is suppressed, and the occurrence of root rot can be prevented. In addition, the bulk density of the hollow particles is 0.90 g / cm 3 By reducing the weight to below 100g, the amount and cost of raw materials can be reduced. In addition, when the hollow particles are used as a medium for cultivating plants, the weight of the medium is reduced, so that the weight of the plant cultivation device containing the medium can be reduced and the workability when moving the device can be improved.
[0028] From the above viewpoint, the bulk density of the hollow particles is 0.80 g / cm 3 Less than 0.50 g / cm is preferred. 3 The following is more preferred: In addition, the bulk density of the hollow particles is 0.10 g / cm because the strength of the hollow particles is superior. 3 More than 0.30 g / cm is preferable. 3 The above is more preferable. When the hollow particles are used as a medium for cultivating plants, the stronger the strength of the hollow particles, the higher the self-supporting property will be, and the easier it will be to handle.
[0029] The bulk density of hollow particles is the bulk density (tap density, unit: g / cm) measured according to the method specified in JIS (Japanese Industrial Standards) K 1201-1 as the "method using a tapping device". 3 ). The bulk density of the hollow particles can be controlled, for example, by adjusting the average particle size of the hollow particles, the thickness of the shell, and the number and size of the through holes formed in the shell. In addition, in the production method of hollow particles described later, the bulk density can also be controlled by changing conditions such as the combination and content of the good solvent and the poor solvent, the solid content of the dope, the drying temperature, and the amount of the solvent in the drying gas during drying, thereby adjusting the pore structure of the shell.
[0030] The average particle size of the hollow particles is not particularly limited and is, for example, 0.1 to 1000 μm. When used as a cultivation medium, the average particle size of the hollow particles is preferably 1 μm or more, more preferably 10 μm or more, in terms of better drainage and easier growth of organs such as roots and rhizomes, and is preferably 800 μm or less, more preferably 600 μm or less, in terms of obtaining a high specific surface area and the associated water retention.
[0031] The average particle size of the hollow particles can be measured by the following method. The hollow particles are observed using a transmission electron microscope (TEM) or a scanning electron microscope (SEM). At this time, the sample, observation conditions, and magnification are appropriately adjusted. At least 100 particles are randomly selected from the obtained observation image, the particle diameters of the selected particles are measured, and the obtained particle diameters are averaged to obtain the average particle diameter. The average particle size of the hollow particles can be controlled by adjusting conditions such as the solids concentration of the dope, the spray pressure of the dope, and the speed of the sprayed droplets in the method for producing hollow particles described below.
[0032] In order to provide hollow particles with superior strength, the ratio t / R of the shell thickness t to the average particle diameter R of the hollow particles is preferably 0.03 or more, more preferably 0.10 or more, and even more preferably 0.13 or more. In addition, in terms of increasing the volume of the cavity, improving water retention, and reducing the weight of the hollow particles, the ratio t / R of the shell thickness t to the average particle diameter R of the hollow particles is preferably 0.40 or less, more preferably 0.30 or less, and even more preferably 0.20 or less.
[0033] [Method of producing hollow particles] The present hollow particles are not particularly limited, and examples thereof include a production method including step 1 of preparing a solution containing TAC, a good solvent, and a poor solvent, and step 2 of spraying the obtained solution to form hollow particles having an outer shell containing TAC.
[0034] <Process 1> Step 1 is a step of preparing a solution (dope) containing TAC, a good solvent, and a poor solvent. For example, step 1 includes a step of putting TAC, a good solvent, and a poor solvent into a container and then mixing them. In step 1, the procedure for adding the above components to the container is not particularly limited. For example, the above components may be added all at once or each component may be added sequentially from the inlet of the container. In addition, when adding one component, it may be added in multiple batches. When each component is added sequentially, the order of addition is not particularly limited, but it is preferable to add the good solvent first, and then add the remaining components sequentially or all at once. When adding TAC to the container, a solution in which TAC has been dissolved in a good solvent in advance may be added.
[0035] In step 1, the mixture contained in the container is preferably stirred using a stirring means to prepare a dope in which each component is uniformly mixed. The stirring method is not particularly limited, and it is preferable to set the stirring means and stirring conditions so that the mixture is sufficiently stirred and the concentration of each component becomes uniform. The temperature of the mixture in the mixing step is not particularly limited, but is preferably 15 to 40° C. The mixing time is not particularly limited, but is preferably 1 to 24 hours in terms of the balance between the uniformity of the resulting dope and the productivity.
[0036] Each component contained in the dope prepared in step 1 will be described. The TAC contained in the dope is as described above. The content of TAC in the dope is not particularly limited, but in terms of better sprayability, the content of TAC (solid content concentration) relative to the total mass of the dope is preferably 1 to 6 mass%, more preferably 1 to 3 mass%.
[0037] (solvent) The dope prepared in step 1 contains a good solvent and a poor solvent as solvents. Here, a "good solvent" means a solvent that dissolves 1 g or more of TAC per liter of solvent at 25° C., and a "poor solvent" means a solvent that dissolves less than 1 g of TAC per liter of solvent at 25° C.
[0038] The good solvent can be used without any particular limitation as long as it satisfies the above-mentioned requirements for a good solvent. Examples of good solvents include dichloromethane, chloroform, acetone, methyl acetate, and ethyl acetate, with dichloromethane being preferred. The good solvent may be used alone or in combination of two or more kinds.
[0039] The poor solvent can be used without any particular limitation as long as it satisfies the above-mentioned requirements for a poor solvent. Examples of poor solvents include N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), benzene, toluene, xylene, methanol, ethanol, 2-propanol, n-butanol, cyclohexane, and water. Of these, N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), benzene, toluene, or xylene is preferred, and N-methyl-2-pyrrolidone (NMP) or dimethylformamide (DMF) is more preferred. The poor solvent may be used alone or in combination of two or more kinds.
[0040] The ratio of the content of the good solvent and the poor solvent is not particularly limited, but the volume ratio of the content of the poor solvent to the total content of the good solvent and the poor solvent is preferably 5 to 30 volume %. By including the poor solvent in the dope in this range of content, the formation of a thin skin layer and the occurrence of wrinkles in the skin layer due to the rapid drying of the solvent in the subsequent step 2 can be suppressed. From the above viewpoints, the volume ratio of the content of the poor solvent to the total content of the good solvent and the poor solvent is more preferably 10 to 25% by volume, and further preferably 15 to 20% by volume.
[0041] The content of the solvent, i.e., the total content of the good solvent and the poor solvent, is not particularly limited, but is preferably 94-99 mass%, more preferably 97-99 mass%, based on the total mass of the dope. The solvent is preferably the remainder of the dope other than TAC.
[0042] As a combination of a good solvent and a poor solvent, a combination in which the difference obtained by subtracting the saturated vapor pressure of the poor solvent from the saturated vapor pressure of the good solvent is 23 kPa or more is preferable, a combination in which the difference is 35 kPa or more is more preferable, and a combination in which the difference is 40 kPa or more is even more preferable. By setting the difference in saturated vapor pressure between the good solvent and the poor solvent within the above range, the dissolving function of the good solvent, which dissolves TAC and has a low saturated vapor pressure, and the function of the poor solvent, which suppresses and delays the formation of a skin layer during the drying process after spraying, are more effectively exhibited, thereby suppressing shrinkage of the skin layer in the later stages of the drying process and more stably forming hollow particles that maintain a spherical hollow shape. The upper limit of the difference is not particularly limited, and is, for example, 60 kPa or less, preferably 55 kPa or less, and more preferably 48 kPa or less.
[0043] For example, when the good solvent is dichloromethane (saturated vapor pressure: 47.4 kPa), poor solvents having a difference in saturated vapor pressure within the above-mentioned preferred range include NMP (saturated vapor pressure: 0.032 kPa), DMF (saturated vapor pressure: 0.35 kPa), water (saturated vapor pressure: 2.3 kPa), and toluene (saturated vapor pressure: 2.2 kPa).
[0044] For example, when the dope contains two or more good solvents, the saturated vapor pressure of each good solvent is converted by the mass of each good solvent contained in the dope, and the average value is used as the saturated vapor pressure of the whole good solvents, and the difference is calculated. The same applies when the dope contains two or more poor solvents.
[0045] In addition, as for the combination of a good solvent and a poor solvent, the distance between the Hansen solubility parameter of the good solvent and the Hansen solubility parameter of the poor solvent is 15.0 MPa 1 / 2The following combination is preferable, and the above distance is 11.3 MPa. 1 / 2 A combination such that the distance is 3.0 MPa or less is more preferable. 1 / 2 More preferably, the distance is 1.6 MPa. 1 / 2 The following combinations are particularly preferred: By setting the distance between the SP values of the good solvent and the poor solvent within the above range, the solubility between the good solvent and the poor solvent is improved, and it is possible to more easily control the rate at which the solvent dries from the droplets sprayed in step 2 and to more easily suppress the formation of a skin layer. From this viewpoint, it is preferable that the TAC-containing solution prepared in step 1 is not phase-separated. The lower limit of the above distance is not particularly limited, and is 0 MPa 1 / 2 It may be more than that.
[0046] In this specification, "Hansen Solubility Parameter" and "SP value" refer to the solubility parameters described in "Hansen Solubility Parameters: A User's Handbook, Second Edition, CMHansen (2007), Taylor and Francis Group, LLC (HSPiP Manual)" and the like, and are values calculated by the following formula using "Practical Hansen Solubility Parameters HSPiP 3rd Edition" (software version 5.1.08) (unit: MPa 1 / 2 ). (SP value) 2 =(δd) 2 +(δp) 2 +(δh) 2 The Hansen solubility parameters express solubility as a multidimensional vector (dispersion term (δd), polarization term (δp), and hydrogen bond term (δh)), and these three parameters can be thought of as the coordinates of a point in a three-dimensional space called the Hansen space. The distance between the Hansen solubility parameters of a good solvent and a poor solvent means the distance between the good solvent and the poor solvent in the Hansen space, and is calculated by the following formula from the dispersion term (δd1), polarization term (δp1), and hydrogen bond term (δh1) of the good solvent, and the dispersion term (δd2), polarization term (δp2), and hydrogen bond term (δh2) of the poor solvent (unit: MPa) 1 / 2 ). (distance)={(δd1-δd2) 2 +(δp1-δp2) 2 +(δh1-δh2) 2} 1 / 2
[0047] For example, when the good solvent is dichloromethane, examples of poor solvents that bring the SP value distance into the above-mentioned preferred range include NMP, DMF, and toluene. For example, when the dope contains two or more good solvents, the center of gravity in the Hansen space is calculated from the SP value of each good solvent and the mass content in the dope, and the SP value of the center of gravity of the good solvent is used to calculate the distance from the SP value of the poor solvent. The same applies when the dope contains two or more poor solvents, and when there are two or more good solvents and two or more poor solvents, the distance between the centers of gravity is the distance between the SP values of the good solvent and the poor solvent.
[0048] The dope may contain other components in addition to the TAC, the good solvent and the poor solvent, such as the above-mentioned cellulose acylate other than TAC. The dope preferably does not substantially contain any other components than TAC, good solvent, and poor solvent. More specifically, the content of the other components than TAC, good solvent, and poor solvent is preferably 1% by mass or less based on the total mass of the dope. The lower limit is not particularly limited, and may be 0% by mass based on the total mass of the dope.
[0049] The viscosity of the dope used in this step can be appropriately selected depending on the production conditions in step 2 (e.g., the method of spraying the dope, the shape of the nozzle used for spraying, and the particle diameter of the desired hollow particles), but the viscosity of the dope at 25°C is preferably 100 to 1000 mPa s.
[0050] <Process 2> Step 2 is a step of spraying the solution (dope) prepared in step 1 to form hollow particles having an outer shell containing TAC.
[0051] The method of spraying the dope in step 2 is not particularly limited as long as it is a known method for forming minute droplets of the dope and drying the formed droplets, and examples thereof include a spray-drying method, a freeze-spray-drying method, a vacuum spray-drying method, and a liquid- or submerged spraying method for spraying droplets from a solidifying solvent or gas into the solidifying solvent. Among them, the spray-drying method is preferred.
[0052] The spray-drying method is a method in which the dope is sprayed using an atomizer, and the resulting fine droplets are dried in a heated dry air stream to form particles. The sprayer used for spraying the dope may be a known sprayer such as a two-fluid nozzle, a one-fluid nozzle, or a disk rotary type. It is preferable to use a sprayer with a narrow spray area and directionality in order to suppress adhesion of droplets to the inner wall of the drying chamber and to produce hollow particles with a more uniform particle size. Examples of such a sprayer include a sprayer equipped with a two-fluid nozzle and a one-fluid nozzle.
[0053] The dope supplied to the atomizer is sprayed, for example, in a drying chamber in which a heated dry air flow flows. The droplets formed by the spraying are dried by the dry air flow, and hollow particles having an outer shell containing TAC are formed. The formed hollow particles are collected by known collection means such as a cyclone or a filter.
[0054] The temperature of the drying air stream is preferably 40 to 250° C., and more preferably 100 to 200° C. By setting the temperature within the above range, it is possible to improve the removal of the solvent and the retention of the hollow shape in a well-balanced manner. The amount of the dope supplied to the nozzle, that is, the amount of the dope sprayed from the nozzle, can be appropriately selected depending on the size and shape of the nozzle and the size of the drying chamber, and is, for example, 0.1 to 10 L / min. When the dope is sprayed using a two-fluid nozzle, the fluid other than the dope discharged from the two-fluid nozzle may be a dry gas. The discharge amount of the dry gas discharged from the two-fluid nozzle is not particularly limited and may be appropriately selected depending on the physical properties of the target hollow particles such as the average particle size, but the ratio of the spray amount Q (L / min) of the dope to the discharge amount (L / min) of the dry gas is preferably 0.001 to 0.3, more preferably 0.01 to 0.2.
[0055] In step 2, the diameter of the droplets formed by spraying the dope (droplet diameter) is preferably 2000 μm or less, more preferably 1000 μm or less. By setting the droplet diameter of the dope to be within the above range, the droplets can be dried more efficiently, and as a result, hollow particles that maintain a hollow structure can be produced more easily. The lower limit of the droplet diameter is not particularly limited, and is, for example, 3 μm or more.
[0056] The direction of the dry air flow in the drying chamber may be a forward direction along the direction in which the dope is sprayed, a reverse direction opposite to the direction in which the dope is sprayed, or a direction intersecting the direction in which the dope is sprayed, but the forward direction is preferable. In step 2, the ratio Q / V of the spray amount Q (L / min) of the solution sprayed in step 2 to the flow rate V (L / min) of the dry airflow flowing in the direction in which the dope is sprayed in the drying chamber is preferably 0.5 or less, more preferably 0.1 or less. By providing a dry airflow of a predetermined amount or more relative to the total amount of droplets to be sprayed, the evaporated solvent can be diffused, the solvent concentration in the airflow can be maintained low, and the droplets can be dried efficiently. As a result, hollow particles that maintain a hollow structure can be produced more easily. The lower limit of the ratio Q / V is not particularly limited, and is, for example, 0.01 or more.
[0057] The use of the hollow particles is not particularly limited, but it is preferable to use the hollow particles as a medium for cultivating plants. The use of the hollow particles as a medium for cultivating plants will be described below.
[0058] [Plant cultivation medium] The medium for plant cultivation of the present invention (hereinafter also referred to as "the medium") contains the hollow particles. The medium contains the hollow particles, which improves water retention and drainage. In addition, the medium has a bulk density of 0.90 g / cm. 3 Since the medium contains the following hollow particles, the weight of the medium is lighter, the weight of the plant cultivation device containing the medium can be reduced, and the workability when moving the device can be improved. Furthermore, since the hollow particles are biodegradable, the medium is easy to dispose of, has a low environmental impact, and can also function as a soil conditioner. From the above viewpoints, the present medium can be preferably applied to the cultivation of plants such as vegetables in an environment where the growth conditions are controlled, such as a plant factory.
[0059] The medium may contain the hollow particles alone, or may contain optional components other than the hollow particles. The optional components are not particularly limited as long as they are natural soil components and known components used in artificial media, and examples thereof include rock wool, perlite, peat moss, wood flour, sawdust, leaf mold, chitin, chitosan, agar, and gellan gum. When the medium contains optional components, the content of the hollow particles is, for example, 50% by mass or more, preferably 90% by mass or more, based on the total mass of the solid content contained in the medium. Here, the solid content means the components contained in the medium other than water.
[0060] This medium is used for cultivating plants. In particular, this medium is preferably used as a seedling medium. There are no particular limitations on the plants cultivated using this medium, and it can be applied to all kinds of plants, such as herbaceous plants, ornamental plants, and woody plants.
[0061] As a method for cultivating plants using the present medium, for example, a method in which a cultivation device including the present medium and a cultivation container for accommodating the present medium is prepared and seeds are sowed in the present medium can be mentioned. The cultivation container is not particularly limited. Examples of the material of the cultivation container include glass and synthetic resins such as polycarbonate. The size of the cultivation container can be appropriately selected depending on the plant to be cultivated and the purpose of cultivation. The seeds used for sowing are not particularly limited, and the method for sowing the seeds in the medium is also not particularly limited, and can be selected from known methods depending on the type of plant. The above-mentioned cultivation method may include a step of supplying water or a nutrient solution to the medium after sowing the seeds in the medium, if necessary.
[0062] The present hollow particles can also be preferably used for purposes other than the above-mentioned culture medium, such as cosmetic raw materials, resin additives, paints, abrasives, weight-reducing agents, and water and oil absorbents. EXAMPLES
[0063] The present invention will be described in more detail below based on examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.
[0064] [Manufacturing of hollow particles] Example 1 Triacetyl cellulose (TAC) (degree of substitution: 2.87) and a mixed solvent containing dichloromethane (good solvent) and N-methyl-2-pyrrolidone (NMP) (poor solvent) with a volume ratio of dichloromethane:NMP of 8:2 were placed in a container and stirred and mixed at room temperature (25°C) for 6 hours to obtain a TAC solution (dope). The content (solid concentration) of TAC relative to the total mass of the obtained solution was 2.0 mass%.
[0065] The above TAC solution adjusted to 25°C was sprayed into dry air at 140°C using a spray dryer equipped with a two-fluid nozzle (B290 manufactured by Nippon Buchi Co., Ltd.) and dried to obtain hollow particles having an outer shell made of TAC. The amount of TAC solution sprayed from the nozzle was 2.5 L / min, and the diameter of the droplets sprayed from the nozzle was 500 μm. Dry air at 140° C. was sprayed from the other outlet of the two-fluid nozzle at a rate of 30 L / min. Dry air was made to flow in the spray direction of the TAC solution near the nozzle in the chamber of the spray dryer. The flow rate V of this dry air flow in the chamber was 50 L / min. Therefore, the ratio Q / V of the spray amount Q (L / min) of the TAC solution sprayed from the nozzle to the flow rate V of the dry air flow flowing in the direction in which the TAC solution is sprayed was 0.05.
[0066] The diameter of droplets sprayed from the nozzle was measured by the following method. A drying container made of heat-resistant glass that transmits visible light was used as the chamber of the spray dryer, and the TAC solution was sprayed under the same conditions as above to produce hollow particles. The vicinity of the nozzle outlet was observed with a high-speed video camera ("speeder V2" manufactured by Photoron Co., Ltd.). 100 droplets were randomly selected from the obtained observation image, and the diameter of each droplet was measured, and the arithmetic average of the obtained measurements was taken as the droplet diameter.
[0067] [Examples 2, 4, 6 and 8] In the method for producing TAC hollow particles described in Example 1, except that the solid content concentration of the dope was changed, TAC hollow particles of Examples 2, 4, 6 and 8, which have shell thicknesses t different from those of Example 1, were produced according to the method described in Example 1.
[0068] [Examples 3 and 7] In the method for producing TAC hollow particles described in Example 1, except that the conditions of the spray amount Q of the dope and the amount of dry air discharged from the two-fluid nozzle were changed, TAC hollow particles of Examples 3 and 7 having an average particle size R different from that of Example 1 were produced according to the method described in Example 1.
[0069] Example 5 In the method for producing TAC hollow particles described in Example 1, except that the solid content concentration of the dope and the spray amount Q of the dope solution were changed, TAC hollow particles of Example 5, which have a different specific surface area from that of Example 1, were produced according to the method described in Example 1.
[0070] Comparative Example 1 A TAC solution was produced according to the method described in Example 1. The TAC solution adjusted to 25°C was poured into a coagulation liquid (distilled water), and the mixture of the TAC solution and the coagulation liquid was stirred at a stirring speed of 1000 rpm using a stirrer to obtain a particle dispersion. The obtained particle dispersion was dried in dry air at 140°C to obtain particles made of TAC. The TAC particles in Comparative Example 1 were solid particles, and their average particle diameter R was 1000 μm.
[0071] Comparative Example 2 The TAC particles of Comparative Example 2 were produced according to the production method described in Comparative Example 1, except that the rotation speed of the stirrer was changed in the production method of TAC particles described in Comparative Example 1. The TAC particles of Comparative Example 2 were solid particles, and their average particle diameter R was 0.9 μm.
[0072] Comparative Example 3 Particles of Comparative Example 3 were produced according to the production method described in Comparative Example 1, except that a dope was used in which a cycloolefin polymer was dissolved in a mixed solvent of dichloromethane and methanol in a volume ratio of 80:20. The particles of Comparative Example 3 were solid particles, and their average particle diameter R was 1000 μm.
[0073] Comparative Example 4 TAC and a mixed solvent containing dichloromethane (good solvent) and methanol (poor solvent) with a volume ratio of dichloromethane:methanol of 6:4 were placed in a container and stirred and mixed at room temperature (25°C) for 6 hours to obtain a TAC solution (dope) of Comparative Example 4. The content (solid concentration) of TAC relative to the total mass of the obtained solution was 2.0 mass%. The TAC particles of Comparative Example 4 were produced in accordance with the method for producing TAC hollow particles described in Example 1, except that the TAC solution of Comparative Example 4 obtained above was used. The TAC particles of Comparative Example 4 were hollow particles, with an average particle diameter R of 500 μm and a specific surface area of 0.01 m 2 / g. In addition, no through holes were formed in the outer shell of the TAC hollow particles of Comparative Example 4.
[0074] Table 1 below shows the composition of the dope used to produce the particles of each Example and Comparative Example, and the production conditions. In the table, the column "Solid content [mass %]" of "Dope composition" indicates the mass ratio (unit: mass %) of the content of the shell material to the total mass of the dope. In the table, the "good solvent" and "poor solvent" columns indicate the type of each solvent used in each Example and Comparative Example. In the table, the column "Solvent ratio" of "Solvent" indicates the content of the poor solvent relative to the total volume of the good solvent and the poor solvent (unit: volume %). In the table, the column "Spray air flow rate [L / min]" under "Manufacturing conditions" indicates the flow rate (unit: L / min) of the dry gas discharged from the two-component nozzle, and the column "Dope spray amount Q [L / min]" indicates the spray amount Q (unit: L / min) of the TAC solution sprayed from the two-component nozzle. In the table, the column "Stirring speed [rpm]" under "Manufacturing conditions" indicates the stirring speed (unit: rpm (revolutions / minute)) when stirring the mixture of the dope and the coagulation liquid in the manufacturing process of the particles of Comparative Examples 1 to 4.
[0075] [Table 1]
[0076] [Measurement and Evaluation] The particles produced in each of the Examples and Comparative Examples were subjected to the following measurements and evaluations.
[0077] <Physical properties of particles> The hollow particles produced in each Example and the solid particles produced in each Comparative Example were measured for the following physical properties. The average particle diameter R and shell thickness t of each particle were measured by the above-mentioned method, and the ratio (t / R) of the shell thickness t to the average particle diameter R was calculated based on each measured value. The bulk density of each particle (unit: g / cm 3 ) was measured according to the method specified in JIS K 1201-1 as described above. The specific surface area of each particle (unit: m 2 / g) was measured by a nitrogen adsorption BET single point method using a specific surface area measuring device ("SA-1000" manufactured by Shibata Rikagaku Co., Ltd.). The measured physical properties of the particles are shown in Table 2 below.
[0078] In addition, when the surfaces of the hollow particles produced in Examples 1 to 8 were observed using an electron microscope, it was found that the shells of these hollow particles had, on average, two or more through holes, and the diameters of these through holes were within the range of 1 to 10% of the average particle diameter of the hollow particles.
[0079] <Strength> The strength of each particle was evaluated by the following method. First, 100 particles were randomly selected from the particles produced in each Example and Comparative Example. In accordance with the method specified in JIS Z 8844 "Method of measuring fracture strength and deformation strength of microparticles," the selected particles were sandwiched between a flat indenter and a sample stage provided in a testing device, and a pressure of 5 MPa was applied to the particles. Next, the external shape of the particles after the test was observed using an electron microscope. Based on the observed appearance of the particles, the particles were classified into those in which deformation of the particles, such as becoming flattened, or damage to the outer shell was observed, and the particles in which neither deformation nor damage to the outer shell was observed, and the particles in which the shape at the time of manufacture was maintained. Next, the ratio (yield) of the number of particles that maintained the shape at the time of manufacture to the total number of particles subjected to the above test was calculated. From the calculated yield, the strength of the particles of each Example and each Comparative Example was evaluated based on the following evaluation criteria.
[0080] (Strength evaluation criteria) A: The rate is 80% or more. B: Profitability is between 50% and 80% C: Profitability is 30% or more but less than 50% D: Profitability is less than 30%
[0081] <Biodegradable> The biodegradability of each particle was evaluated by the biodegradation rate obtained by the following method. The biodegradation rate was measured by a method using activated sludge according to JIS K 6950. Activated sludge obtained from a municipal sewage treatment plant was left for about 1 hour to obtain a supernatant (activated sludge concentration: about 360 ppm). After about 300 mL of the above supernatant was placed in a culture bottle, 30 mg of a particle sample of each Example and each Comparative Example was added to the culture bottle. The measurement was started when the particle sample was added, and the biochemical oxygen demand (BOD) in each culture bottle was measured every 24 hours while stirring the mixed liquid. The above BOD was measured a total of 31 times until 720 hours after the measurement started, that is, 30 days later. The BOD was measured using a coulometer "OM3001" manufactured by Okura Electric Co., Ltd. The biodegradation rate (mass%) of the particle sample was calculated by calculating the ratio of the BOD measured 720 hours after the start of measurement to the theoretical BOD when the particle sample was completely decomposed based on the chemical composition of the particle sample. From the obtained biodegradation rate, the biodegradability of the particles of each Example and Comparative Example was evaluated based on the following evaluation criteria.
[0082] (Biodegradability evaluation criteria) A: Biodegradation rate is 60% by mass or more B: Biodegradation rate is 40% by mass or more but less than 60% by mass C: Biodegradation rate is 10% by mass or more but less than 40% by mass D: Biodegradation rate is less than 10% by mass
[0083] <Water retention> The water retention of each particle was evaluated by the following method. Each particle is weighed at approximately 90 kg / m 3 A container was prepared, filled with particles to a density of 0.01g / cm2. Water was added to the container to saturate it with water. The average water saturation (the volume ratio of the amount of water held in the particle-packed layer to the total pores in the particle-packed layer of the container) of the particles packed in the container was calculated using the following formula. Average water saturation (%) = {weight of packed bed of particles after water saturation (g) - dry weight of particles (g)} / {volume of packed bed of particles after water saturation (cm 3 )-particle dry weight (g) / 1.3}×100 Based on the results of another measurement, the true specific gravity of TAC was determined to be approximately 1.3, and that of water was determined to be 1.0. The "average" in the average water saturation degree means that the water saturation degree is the average value of the water saturation degree of the entire particle layer, since the moisture content often varies between the upper and lower layers of the packed particle layer. The "dry weight of particles" above means the weight of each particle after a thorough drying process. The water retention of the particles of each Example and Comparative Example was evaluated based on the average water saturation of the obtained particles and on the following evaluation criteria.
[0084] (Water retention evaluation standard) A: Average water saturation is 50% or more B: Average water saturation is between 30% and 50% C: Average water saturation is 5% or more but less than 30% D: Average water saturation is less than 5%
[0085] <Drainage> Using each particle, the saturated hydraulic conductivity was measured according to the falling head method defined in JIS A 1218. From the measured saturated hydraulic conductivity, the drainage properties of the particles of each Example and Comparative Example were evaluated based on the following evaluation criteria.
[0086] (Drainage evaluation criteria) A: Saturated hydraulic conductivity is 1×10 -3 m / s or more B: Saturated hydraulic conductivity is 1×10 -5 m / s or more 1×10 -3 Less than m / s C: Saturated hydraulic conductivity is 1×10 -5 Less than m / s
[0087] <Ease of handling> The handleability of each particle as a medium was evaluated by the following method. That is, in the medium obtained using each particle, sowing and seedlings were carried out according to the test method for evaluating root growth described below, and then the medium was removed. The shape of each particle in the removed medium was observed using an electron microscope. If the observation showed that the shape of the particle after the test was almost maintained, the handleability of the particle was evaluated as "A", and if many particles were observed to be partially damaged, the handleability of the particle was evaluated as "B".
[0088] <Root growth> The root growth of plants grown using each particle as a medium was evaluated by the following method. Each particle was spread in a tray to form a medium. Tomato seeds (variety "Momotaro") were sown in a staggered pattern on this medium and cultivated in a glass greenhouse. Tap water was provided at appropriate times until the cotyledons developed, and after the cotyledons developed, a culture solution (a diluted culture solution obtained by diluting the culture solution "Otsuka A Formula" manufactured by Otsuka Chemical Co., Ltd. to a concentration of 1 / 4) was provided to the medium by the bottom watering method once or twice a day. For the seedlings when the third true leaf developed, the direction and area in which the roots had grown in the medium were observed, and the root growth was evaluated based on the observation results and the following evaluation criteria.
[0089] (Root growth evaluation criteria) A: The roots grow in all directions with almost no bias. B: The roots are growing in all directions, but there is some bias in the root growth. C: Root growth was inhibited in some directions, and growth was insufficient.
[0090] Table 2 below shows the particle structures and the above evaluation results of each of the examples and comparative examples. In the table, in the "Type" column of "Particle," "hollow" means hollow particles, and "solid" means solid particles. In the table, the column "Ratio t / R" indicates the ratio (t / R) of the shell thickness t to the average particle diameter R of the particles.
[0091] [Table 2]
[0092] As shown in Table 2, it was confirmed that the TAC hollow particles according to the present invention have excellent water retention and drainage properties.
[0093] It was confirmed that when the ratio t / R of the shell thickness t to the average particle diameter R of the hollow particles was 0.10 or more, the strength of the hollow particles was superior (comparison between Examples 2 and 6), and when the ratio t / R was 0.13 or more, the strength of the hollow particles was even superior (comparison between Examples 1 and 2). Furthermore, it was confirmed that when the ratio t / R was 0.30 or less, the water retention of the hollow particles was superior (comparison between Examples 4 and 8), and when the ratio t / R was 0.20 or less, the water retention of the hollow particles was even superior (comparison between Examples 1, 4 and 8).
[0094] The bulk density of the hollow particles is 0.50 g / cm 3 It was confirmed that the hollow particles have better drainage properties when the ratio is below 100 (comparison between Examples 1 and 4).
[0095] The specific surface area of the hollow particles is 0.025m 2 / g or more, the water retention of the hollow particles was confirmed to be superior (comparison between Examples 1 and 5).
[0096] It was confirmed that when the average particle size R of the hollow particles is 50 μm or more, the root growth is superior (comparison between Examples 1 and 3).
Claims
1. A hollow particle having an outer shell comprising triacetyl cellulose, The outer shell has a through hole penetrating the outer shell in a thickness direction, The specific surface area of the hollow particles is 0.02 m 2 / g or more, The bulk density of the hollow particles is 0.90 g / cm 3 is as follows: The hollow portion surrounded by the outer shell has a spherical shape, the pore size of the through holes is 1 to 10% of the average particle size R of the hollow particles, The ratio t / R of the thickness t of the outer shell to the average particle diameter R of the hollow particles is 0.03 to 0.
40.
2. 2. The hollow particles according to claim 1, wherein a ratio t / R of a thickness t of the outer shell to an average particle diameter R of the hollow particles is 0.10 to 0.
40.
3. The bulk density of the hollow particles is 0.30 to 0.90 g / cm 3 The hollow particle according to claim 1 or 2,
4. The specific surface area of the hollow particles is 0.02 to 5 m 2 The hollow particle according to any one of claims 1 to 3, wherein the molecular weight of the hollow particle is 1 / g.
5. 5. The hollow particles according to claim 1, wherein a ratio t / R of a thickness t of the outer shell to an average particle diameter R of the hollow particles is 0.13 to 0.
40.
6. The hollow particles according to any one of claims 1 to 5, wherein the average particle size R of the hollow particles is 1 to 600 µm.
7. A medium for cultivating plants, comprising the hollow particles according to any one of claims 1 to 6.
Citation Information
Patent Citations
JP1973052849A
Process for preparing porous cellulose beads
JP1977129788A
Production of microcapsule of improved hydrophilic nature
JP1980129145A
Production of spherical particle
JP1988095238A
Method for manufacturing fine porous cellulose particles
JP1990053801A